ANALISIS SEKTOR UNGGULAN DALAM PENYERAPAN TENAGA KERJA DI KABUPATEN MINAHASA SELATAN - Andrew ., Lahama; Leonardus R. Rengkung; Eyverson ., Ruauw (Sam Ratulangi University, 2018)
This study aims to analyze the leading sectors in the absorption of labor and to know the contribution of the leading sector in the absorption of labor in south Minahasa Regency. The research was conducted for two months starting from months January to months Ferbruay 2018. The date used in this study is secondary date obtained from the Central Bureau of Statistics (BPS) South Minahasa Regency. The date is processed using location quotient analysis (LQ) and the date is presented in table and described descriptively. The research results show that the leading sectors in the absorption of labor in South Minahasa Regency are the processing industry sector, electricity, gas and drinking water sector; and agriculture sector. The first sector with the highest average LQ is the processing industry sector with an average value of LQ 2.22. The second seeded sector is the electricity, gas and dringking water sector with an average LQ of 1.50 and the third leading sector is the agricultural sector with an average LQ of 1.23. The processing industry sector, electricity, gas and dringking water sector and agriculture sector become the leading one because it has LQ value more dominant in the absorption of manpower that the sector the same in north sulawesi province.*er*.